Sensitive Blood-Based Detection of Asbestos-Associated Diseases Using Cysteine-Rich Angiogenic Inducer 61 as Circulating Protein Biomarker. (18th December 2020) - Bartkowiak, Kai; Casjens, Swaantje; Andreas, Antje; Ačkar, Lucija; Joosse, Simon A; Raiko, Irina; Brüning, Thomas; Geffken, Maria; Peine, Sven; Johnen, Georg; Weber, Daniel Gilbert; Pantel, Klaus
Abstract: Background: Detection of asbestos-associated diseases like asbestosis or mesothelioma is still challenging. We sought to improve the diagnosis of benign asbestos-associated disease (BAAD) by detection of the protein cysteine-rich angiogenic inducer 61 (Cyr61) in human plasma. Methods: Plasma Cyr61 was quantified using an enzyme-linked immunosorbent assay. Plasma samples from males diagnosed with BAAD, but without a malignant disease ( n  = 101), and malignant mesothelioma ( n  = 21; 15 males, 6 females), as well as nonasbestos-exposed healthy control participants ( n  = 150; 58 males, 92 females) were analyzed. Clinical sensitivity and specificity of Cyr61 were determined by receiver operating characteristic analysis. Results: The median plasma Cyr61 concentration for healthy control participants was 0.27 ng/mL. Cytoplasmic Cyr61 in peripheral blood mononuclear cells from healthy control participants was evenly distributed, as detected by immunofluorescent staining. The increase in plasma Cyr61 concentrations in the BAAD study group was statistically significant compared to the healthy control participants ( P  < 0.0001). For the detection of BAAD vs male healthy control participants, clinical sensitivity was 88% and clinical specificity 95% with an area under the curve of 0.924 at maximal Youden Index. For a predefined clinical specificity of 100%, the clinical sensitivity was 76%. For male mesothelioma patients vs male healthy control participants, the clinical sensitivity at maximal Youden Index was 95% with a clinical specificity of 100% (area under the curve, 0.997) and for a predefined clinical specificity of 100%, the clinical sensitivity was 93%. Conclusions: In our study, plasma Cyr61 protein concentrations showed to be a new biomarker for asbestos-associated diseases like BAAD and mesothelioma in men, which deserves further investigation in large-scale cohort studies.